Chinese Reverse Glass Painting 1720-1820 : An Artistic Meeting Between China and the West. Preface by Danielle Elisseeff. - Audric, Thierry (Bern : Peter Lang AG International Academic Publishers, 2020)
Displaying a talent for combining aesthetic sensibility with scientific rigor, the author has given new life to something that once excited European passions: an original, non-academic art at the forefront of the 'new technology' of the time.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books